OPTIMALISASI INSTAGRAM SEBAGAI MEDIA DIGITAL MARKETING DI ROSALIA INDAH: DIGITAL MARKETING AT ROSALIA INDAH - Matthew Ervino Setiawan; Suparwi Suparwi; Bartolomeus Herawan Mintardjo; Emmelia Nadira Satiti (LPPM Politeknik Pajajaran ICB Bandung, 2025)
The development of information and communication technology has led to changes in marketing strategies, especially in transportation and tourism. Social media, particularly the Instagram platform, has become an effective tool for conveying marketing messages visually and interactively to consumers through uploaded content. This study aims to investigate how Rosalia Indah utilizes the Instagram platform as a digital marketing medium and to identify the factors driving Rosalia Indah's use of the Instagram social media platform. This study employs a descriptive qualitative research method, with data collection techniques including in-depth interviews with Rosalia Indah staff, direct field observations, documentation, and literature review. Data validity was tested using triangulation techniques. The main informants or respondents were Rosalia Indah Kleco marketing staff, including supervisors and managers of the tour and travel division. Based on the results obtained, Instagram is actively used by Rosalia Indah to offer or promote tour packages, transportation tickets, and others. The content uploaded is tailored to the target audience based on age, gender, location, and seasonal trends. The driving factors for using Instagram include ease of access, effectiveness in reaching the audience through interactive features such as Instagram Ads or Meta Ads and Insights, as well as relatively low costs compared to traditional methods like newspapers or billboards. The use of Instagram has proven to enhance brand awareness and strengthen communication with consumers. Keywords: Digital Marketing, Marketing Communication, Instagram, Social Media, Brand Awareness